Uji Aktivitas Tabir Surya Pada Ekstrak Etanol Kulit Ubi Jalar Ungu (Ipomoea batatas L) dengan Metode Spektrofotometri - Febriani, Amelia; Sholikha, Munnawarohthus; Nurhasanah, Sari (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2025)
Excessive exposure to ultraviolet (UV) radiation from sunlight can cause harmful effects on the skin, such as erythema, pigmentation, premature aging, and even skin cancer. Therefore, the use of sunscreen is an important preventive measure. This study was conducted to evaluate the potential of purple sweet potato peel extract (Ipomoea batatas L.) as a natural active ingredient in sunscreen formulations. Purple sweet potato peel contains anthocyanin pigments, known for their antioxidant activity and ability to absorb UV rays. The extraction process was carried out using the maceration method with 70% ethanol as the solvent. Phytochemical screening revealed the presence of flavonoids, alkaloids, and steroids in the extract. The sunscreen potential was assessed in vitro using UV-Vis spectrophotometry at a wavelength range of 290–320 nm to determine the Sun Protection Factor (SPF) value. The results showed that the extract had the highest SPF value of 1.731 at a concentration of 400 ppm, which falls into the minimal protection category. Although the level of protection is still low, these findings indicate the initial potential of purple sweet potato peel extract as a natural UV-protective agent that is eco-friendly and readily available in Indonesia